West Sumatra Men's Cricket Team Batting Performance Analysis - Romi Mardela; Eri Barlian; Gusril Gusril; Yendrizal Yendrizal; Anton Komaini; Yudi Alfa Ritsi (Jurnal Sporta Saintika, 2025)
Twenty20 (T20) Cricket matches are one of the National Championship, BK PON, and PON for the Province Cricket Championship. Meanwhile, since the West Sumatra Men's Cricket Team participated in the 2014 National Championship until the BK PON in 2023, this team never reached the podium in that event. Even in the last BK PON, they lost in the group stage. This team also lost in other events, so they failed to qualify for the 2024 PON. This study aims to analyze the causes of the West Sumatra Man Cricket Team's defeat in the T20 event, through match statistics. This study is a descriptive study with the object of research of the West Sumatra Men's Cricket Team, consisting of 14 athletes, in the T20 match, facing three opposing teams (Banten, West Java, and East Kalimantan). The instruments used include match statistics, especially the number of team runs and individual runs during the batting innings, which are analyzed through the Indonesian Cricket Association website and video recordings of matches. The results obtained in the T20 event of the West Sumatra Men's Cricket Team from individual statistics (Batting) show that the performance of each athlete is not very good compared to the opposing team, so the team cannot achieve victory. Further research is needed to compare the performance of the West Sumatra Men's Cricket Team with the winning team in the T20 event.